Đạo hàm của hàm số \(y=\left(x^2+4x+3\right)\mathrm{e}^{2x}\) là
\(y'=\left(4x+8\right)\mathrm{e}^{2x}\) | |
\(y'=\left(x^2+6x+7\right)\mathrm{e}^{2x}\) | |
\(y'=\left(2x^2+10x+10\right)\mathrm{e}^{2x}\) | |
\(y'=\left(-2x^2-6x-2\right)\mathrm{e}^{2x}\) |
Chọn phương án C.
Dùng máy tính cầm tay:
Chọn phương án C.
\(\begin{aligned}
y'&=\left(x^2+4x+3\right)'\mathrm{e}^{2x}+\left(x^2+4x+3\right)\left(\mathrm{e}^{2x}\right)'\\
&=(2x+4)\mathrm{e}^{2x}+\left(x^2+4x+3\right)2\mathrm{e}^{2x}\\
&=\left(2x+4+2x^2+8x+6\right)\mathrm{e}^{2x}\\
&=\left(2x^2+10x+10\right)\mathrm{e}^{2x}.
\end{aligned}\)